Energy-based metric for analysis of organic PV devices in comparison with conventional industrial technologies. (October 2018) - Gracia-Amillo, Ana M.; Bardizza, Giorgio; Salis, Elena; Huld, Thomas; Dunlop, Ewan D.
Abstract: The emerging thin-film photovoltaic (PV) technologies show the potential to compete in the future market with the currently dominant crystalline silicon (c-Si) technology. A comparison of the different technologies based on their module performance rated at Standard Test Conditions (STC) is a commonly accepted method in the PV community. However, despite being a useful tool, it does not give enough information to accurately predict how much energy a PV module would deliver in the field when subjected to the wide range of real operating conditions. In this paper we explore a potential screening method for new PV technologies; an energy-based metric to estimate the energy performance (Module Performance Ratio) of a PV module in a certain climate. This is constructed on the basis of validated models, and rigorous power rating measurements performed in controlled laboratory conditions at different temperature and irradiance levels. This method has the advantage that it can be applied to laboratory prototypes of technologies still in development as it does not require that the final product has reached maturity. The method has been applied to three thin-film PV technologies including the very innovative organic photovoltaics (OPV), and a comparison with c-Si is presented. The results obtained from the module performance ratio estimation in five different locations show how the emerging OPV technology performs similarly to some of the most common technologies considered and even outperforms slightly some technologies in some of the studied locations. These results could reinforce and support further development of this technology and its potential applications.